Sugarcane bagasse ash as fertilizer for soybeans: Effects of added residues on ash composition, mineralogy, phosphorus extractability and plant availability - Dombinov, Vitalij; Herzel, Hannes; Meiller, Martin; Müller, Felix; Willbold, Sabine; Zang, Joachim W.; da Fonseca-Zang, Warde A.; Adam, Christian; Klose, Holger; Poorter, Hendrik; Jablonowski, Nicolai D.; Schrey, Silvia D. (Frontiers in Plant Science, 2022)
Sugarcane bagasse is commonly combusted to generate energy. Recycling strategies rarely consider the resulting ash as a potential fertilizer. To change this for a sustainable circular economy, we evaluated bagasse ash as a fertilizer for soybeans under greenhouse conditions. Furthermore, we investigated the effects of co-gasification and co-combustion of bagasse with either chicken manure or sewage sludge on increasing phosphorus mass fraction, and extractability and mineral phosphorus phases to understand and predict phosphate availability from ashes to soybeans. The fertilizer efficiency of pure bagasse ash increased with the dose supplied. Nevertheless, it was not as effective as fertilization with triple-superphosphate and K2SO4, which we attributed to lower phosphate availability. Co-gasification and co-combustion increased phosphorus mass fraction in all bagasse-based ashes, but its extractability and availability to soybeans increased only when co-processed with chicken manure because it enabled the formation of Ca-alkali phosphates. Therefore, we recommend co-combusting biomass with alkali-rich residues to increase the availability of phosphate from the ash to plants.